RESPON MAHASISWA IAIN PONOROGO TERHADAP BERITA HOAXS PEMILU 2024 DI MEDIA SOSIAL - Siti Maisaroh; Zakariya Putra Pratama; Andhita Risko Faristiana (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Elections are important moments in the democratic life of a country, where the people have the opportunity to choose their leaders and representatives. In an increasingly advanced digital era, social media has become a significant platform for influencing public opinion and shaping public opinion. Therefore, we want to see the response from the community that we represent to students, because students understand more about science. This research is a manifestation of the university's concern in encouraging students to use social media wisely. So that students are able to manage healthy and rational information about the dangers of hoax news. The aim of this research is to find out how much students care about the 2024 election hoax news around them, especially on social media. This research method uses uses and gratification theory and agenda setting theory. This research was carried out by conducting interviews with IAIN Ponorogo students in each faculty, represented by 1 person. The results of this research are that there are still students who ignore the news about the 2024 election and there are students who cross-check the news they get about the 2024 election to find the truth of the news. The conclusion of this research is that there are still many students who are ignorant of the news of the 2024 election, even though they are students who are said to be agents of change who should have a sensitive, caring soul and an imagination for a better life. However, there are still students who care about the truth of the news, because according to them the news can be set by someone and the news can change someone's direction of thinking.